2003
DOI: 10.1080/11250000309356488
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and immunohistochemistry of the caudal neurosecretory system in tetraodontids

Abstract: Although the structural organization of the caudal neurosecretory system (CNSS) has been described in more than 450 teleosts, there are still no data available for tetraodontids. In the present paper, the morphological organization of the CNSS is described in two puffer fish, Tetraodon fluviatilis and T. palembangensis, by using a histological method selective for caudal secretion and oCRF/UI (ovine corticotropin-releasing factor/urotensin I) immunohistochemical staining. In tetraodontids, the caudal spinal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Therefore, the BrdUlabeled cells might partially be the regenerative neuroblasts, and the increased UI-positive Dahlgren cells might not be differentiated from newly regenerative neuroblast cells. Previous morphology and immunohistochemistry studies of the CNSS have found that CRH and UI were co-expressed (Cioni and Bordieri, 2003;Lu et al, 2004). Meanwhile, UI and UII could also be co-expressed in a fraction of Dahlgren cells (Parmentier et al, 2006).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Therefore, the BrdUlabeled cells might partially be the regenerative neuroblasts, and the increased UI-positive Dahlgren cells might not be differentiated from newly regenerative neuroblast cells. Previous morphology and immunohistochemistry studies of the CNSS have found that CRH and UI were co-expressed (Cioni and Bordieri, 2003;Lu et al, 2004). Meanwhile, UI and UII could also be co-expressed in a fraction of Dahlgren cells (Parmentier et al, 2006).…”
Section: Discussionmentioning
confidence: 87%
“…However, until now, it was not known whether alterations in temperature would affect the number of Dahlgren cells and their associated secretions. Morphology and immunohistochemistry studies of the CNSS suggested that CRH, UI and UII were produced and secreted from the Dahlgren cells in the CNSS (Cioni and Bordieri, 2003;Lu et al, 2004). Therefore, the number of CRH-, UI-and UII-positive Dahlgren cells could represent the required secretory level of these genes in CNSS.…”
Section: Discussionmentioning
confidence: 99%